An empirical analysis of lean six sigma implementation in SMEs – A migratory perspective - Thomas, Andrew; Ringwald, Kath; Parfitt, Scott; Byard, Paul (Cranfield University Press, 2013)
The purpose of this paper is to investigate the migratory nature of Lean Six Sigma (LSS) implementation in manufacturing based SMEs in the UK. The companies were surveyed at two points over a five year period. These periods were before and after the 2008 recession point and were identified in order to assess the level of LSS implementation as a result of the tougher economic climate that has prevailed in the manufacturing industry since 2008. Analysis is carried out on a sample of 96 manufacturing SMEs from a range of manufacturing sectors in the UK. Data was gathered from company CEOs via a triangulated method of questionnaire, direct observation and interviews. The findings show the dynamic nature of LSS implementation in SMEs. Further work will be required to extend the LSS categorisation system to provide a wider category set that further defines the dynamical nature of LSS implementation.
Keywords: Lean Six Sigma; Strategy Migration; Paradigm Adoption